The psychology of ultra-marathon runners: A systematic review - Roebuck, G. S.; Fitzgerald, P. B.; Urquhart, D. M.; Ng, S. K.; Cicuttini, F. M.; Fitzgibbon, B. M. (Psychology of Sport and Exercise, 2018)
Objectives: An `ultra-marathon` is a footrace over a distance >42.2km. There is considerable interest in the psychological characteristics of ultra-marathon runners (`ultra-runners`) and the psychological effects of running an ultra-marathon. This review aimed to summarise the existing literature concerning the psychology of ultra-runners. Design: A systematic review was performed. Studies were included if they investigated ultra-runners` personality traits, mood, cognitive processes, cognitive function, pain perception, motivations, phenomenology, psychopathology or response to sports psychology interventions. Method: Four databases (PubMed, Scopus, Web of Science and PsycINFO) were searched electronically up until December 2017. Results: Fifty-one studies met the inclusion criteria. A few conclusions regarding the psychology of ultra-runners may be drawn from these studies. First, the acute mood effects of ultra-running appear to include an increase in fatigue and a decrease in vigour and tension. Secondly, the most important factor motivating ultra-runners to engage in their sport appears to be the opportunity to achieve personal goals. Finally, ultra-running seems to be associated with a psychological drive to explore physical and mental limits. Conclusions: Although the existing literature sheds some light on ultra-runners` mood states, motivations and phenomenology, further high-quality studies investigating the psychology of these remarkable athletes are needed.